Αποκεντρωμένη μονάδα επεξεργασίας αστικών λυμάτων - επαναχρησιμοποίηση επεξεργασμένων εκροών - Γεωργίου, Στέλιος (Τμήμα πολιτικών μηχανικών και μηχανικών γεωπληροφορικης, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Water is a fundamental substance in insuring life existence and its maintenance. Water is also crucial in human beings nutrition as well as is the essential raw material of the primary and secondary production. By primary production we mean agriculture and animal stock raising, and the secondary production refers to the water use as an industrial material. It turns out that water as a natural resource is included in any production - development process. It determines any country's production power, the ability or inability of productive activity expansion, and also its efficiency. However, as the world population grows and the production of goods expands, water becomes increasingly valuable. Water is a natural material, it is not a result of, for instance, harvesting as other natural resources such as solar power or wind power, moreover, it has a particular social and cultural value. Even though, the majority of our planet's surface is covered with water, a lot of it is rich in dissolved salts (sea water), thus is not appropriate to satisfy essential human needs (drinking). Only a very small percentage of a ground and surface water is suitable for human use. It should also be mentioned that the access to the water which is suitable for human use depends on the weather conditions, the natural supply, demand and interventions of humans particularly in the water’s quality. The negative changes in water quality always result in the reduction or complete prohibition of the water usage. The Civil, Chemical and Environmental Engineering are the fields that contribute to the quality control of water, the choice of the water treatment method used, making water suitable for drinking or achieving specific quality requirements for industrial applications. The introduction of this thesis provides an insight in the importance of water in social and economic advancement of human history and the nessecity of water protection, it also emphasizes the limits of available water levels to be exploited. It explains how human interventions affect the global water balance and discusses the overall negative effects of humanity on water. The following literature review provides a brief history on the subject of sewage management which is analyzed from the point of two major categories - the collection and treatment of urban waste water (centralized, decentralized). The characteristics of each system, the pros and cons and a graphical representation of both are also discussed in this chapter. The wastewater treatment process is divided into three stages. Primary, secondary and tertiary treatment with disinfection. This thesis analyzes different methods of water treatment, the characteristic output of each method as well as each stage relation to each other. Further, we analyze various methods of the treated water disposal and the criteria that determine disposal method. Another outcome of the urban water treatment is sludge, and consecuently, various methods of sludge treatment and disposal are also analysed in this work. The final chapter explains the pilot decentralized wastewater treatment plant based on load characteristics of the waste water provided by Mr. Theocharous Kyriakos (Chemical Engineer SBLA), as well as the data regarding the capacity of each hotel and water effluent by Mr.Papamichael Giannis (Assistant Director at Atlantica Hotel). Once the wastewater treatment plant and its operation are analyzed, we discuss why it is more economical to do decentralized water treatment system and last we mention different methods for re-using treated water and sludge.
Keywords: Water; Water Quality Control; Sewage Management; Wastewater treatment process; Νερό; Ποιοτικός Έλεγχος Νερού; Διαχείριση Λυμάτων; Διεργασίες Επεξεργασίας Αστικών Λυμάτων; Προστασία Υδάτων